Front Cover: Titanium Vacancies in TiO2 Nanofibers Enable Highly Efficient Photodriven Seawater Splitting (Chem. Eur. J. 57/2021) - Zhang, Yan‐Xiang; Wu, Si‐Ming; Tian, Ge; Zhao, Xiao‐Fang; Wang, Li‐Ying; Yin, Yi‐Xia; Wu, Lu; Li, Qian‐Ni; Zhang, Yue‐Xing; Wu, Jin‐Song; Janiak, Christoph; Ozoemena, Kenneth I.; et al. (Chemistry : a European journal, 2021)
Rich Ti vacancies in TiO2 nanofibers are presented in the Full Paper by X.‐Y. Yang and co‐workers (DOI: 10.1002/chem.202101817). The unidirectional electron trap and directional H+ adsorption ability of Ti vacancies enable efficient charge transfer and resistance to the corrosion of seawater. They thus contribute excellent activity and long‐time stability to photodriven seawater splitting, opening a door to marine applications of semiconductors.